Simultaneous identification and estimation of glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid in de‐glycyrrhized Ayurvedic lipid‐based formulation of Glycyrrhiza glabra using dual wavelength reverse phase‐high‐performance liquid chromatography. Issue 10 (19th August 2020) - Kumbhalkar, Bhagyashri; Walunj, Tanhaji; Chavan, Sandeep; Gupta, Vidya; Deshmukh, Vineeta; Sardeshmukh, Sadanand
Abstract: Plant‐based Ayurvedic formulations such as medicated oils, confectioneries, etc. are developed with a rationale of selecting specific compounds for targeted action and minimal side effects. It is imperative to develop an analytical method to simultaneously identify and quantify the targeted compounds for good resolution with low retention time. The present assay using reverse phase‐high‐performance liquid chromatography is optimized to resolve glycyrrhizin, glabridin, and 18β‐glycyrrhetinic acid simultaneously at retention times of 6.6, 8.1, and 10.2 min, respectively, using acidified mobile phase from Glycyrrhiza glabra utilized in Ayurvedic lipid (cow's ghee and sesame oil) based formulations. Raw material, its decoction, and residues formed during preparation steps were extracted in methanol while lipid formulations were extracted using a binary solvent system of methanol and n ‐hexane. The separation was performed on Hypersil gold column maintained at 40°C using 0.2% ortho‐phosphoric acid with pH 3.5 in water and acetonitrile as binary gradient mobile phase. The compounds were detected at wavelengths 230 (glabridin) and 254 (glycyrrhizin and 18β‐glycyrrhetinic acid) nm. The method revealed de‐glycyrrhized finished products containing glabridin and 18β‐glycyrrhetinic acid having medicinal value.